(ax - 4)(bx - 2y)
(ax + b)(x - 8y)
(ax - 2y)(bx - 4)
(bx - 4)(ax - 2y)
(abx - 4)(x - 2y)
Correct answer is A
abx2 + 8y - 4bx - 2axy = (abx2 - 4bx) + (8y - 2axy)
= bx(ax - 4) 2y(ax - 4) 2y(ax - 4)
= (bx - 2y)(ax - 4)
Evaluate 3(x + 2) > 6(x + 3)...
A die with faces numbered 1 to 6 is rolled once. What is the probability of obtaining 4?...
In the diagram, /PQ/ = /QR/ and /PR/ = /RS/ = /SP/, calculate the side of < QRS ...
Calculate the mean deviation of the first five prime numbers. ...
Find the values of y for which the expression y2−9y+18y2+4y−21 is undefined...
A binary operation ⊕ is defines on the set of all positive integers by a ⊕ b = ab ...
If p and q are two non zero numbers and 18(p+q) = (18+p)q, which of the following must be true? ...